2008
DOI: 10.1111/j.1472-765x.2008.02433.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of swabbing and destructive methods for microbiological pig carcass sampling

Abstract: Aims:  To compare the Belgian swabbing sampling method for pig carcasses with the reference destructive method with regard to Escherichia coli and aerobic plate counts, Salmonella and Campylobacter prevalence and their relationship. Methods and Results:  Recovery was significantly lower for the swabbing method and corresponded to a recovery of 36% for E. coli counts and 81% for aerobic plate counts in comparison with the destructive method. There was no significant difference between the swabbing and destructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…This is in line with other studies carried out on pig carcases (Ghafir & Daube, 2008;Lindblad, 2007;Martinez, Celda, Anastasio, Garcia, & Lopez-Mendoza, 2010;Pepperell et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with other studies carried out on pig carcases (Ghafir & Daube, 2008;Lindblad, 2007;Martinez, Celda, Anastasio, Garcia, & Lopez-Mendoza, 2010;Pepperell et al, 2005).…”
Section: Discussionsupporting
confidence: 93%
“…On carcases of cattle, it has been shown, that the double swab technique produced lower colony counts than the excision method (Cenci-Goga et al, 2007). In pigs, swab sampling and excision have mostly been compared for Enterobacteriaceae, Campylobacter and total bacterial counts with swabbing methods leading to lower recovery rates (Ghafir & Daube, 2008;Lindblad, 2007;Pepperell et al, 2005). It has been pointed out, that sampling methods for certain bacteria should be carefully selected after validation trials (Cenci-Goga et al, 2007) and depend on the contamination levels (Louwers & Klein, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that recovery of bacteria from a carcass surface was dependent on the sampling method used (Gill and Badoni 2005; Ghafir and Daube 2008). The lowest recovery number and highest variation were achieved by swabbing, suggesting that swabbing was the poorest method.…”
Section: Resultsmentioning
confidence: 76%
“…Thus, most researchers prefer nondestructive methods for recovering bacteria from carcass surfaces. In studies of swine carcasses (43,60), swabbing of a large surface can be at least as sensitive as the destructive excision method. However, the swabbing technique has inherent variability and the results obtained depend on the material used for swabbing (64,66), the pressure exerted during application, the time span, and the sample collector's skills (25).…”
Section: Salmonella Prevalence In Carcassesmentioning
confidence: 99%